The functional connectivity of language network across the life span: Disentangling the effects of typical aging from Alzheimer’s disease - Rafiq, Marie; Jucla, Mélanie; Guerrier, Laura; Péran, Patrice; Pariente, Jérémie; Pistono, Aurélie (Frontiers in Aging Neuroscience, 2022)
Language is usually characterized as the most preserved cognitive function during typical aging. Several neuroimaging studies have shown that healthy aging is characterized by inter-network compensation which correlates with better language performance. On the contrary, language deficits occur early in the course of Alzheimer’s disease (AD). Therefore, this study compares young participants, healthy older participants, and prodromal AD participants, to characterize functional connectivity changes in language due to healthy aging or prodromal AD. We first compared measures of integrated local correlations (ILC) and fractional amplitude of low-frequency oscillations (fALFF) in language areas. We showed that both groups of older adults had lower connectivity values within frontal language-related areas. In the healthy older group, higher ILC and fALFF values in frontal areas were positively correlated with fluency and naming tasks. We then performed seed-based analyses, for more precise discrimination between healthy aging and prodromal AD. Healthy older adults showed no functional alterations at a seed-based level when the seed area was not or only slightly impaired compared to the young adults (i.e., inferior frontal gyrus), while prodromal AD participants also showed decreased connectivity at a seed-based level. On the contrary, when the seed area was similarly impaired in healthy older adults and prodromal AD participants on ILC and fALLF measures, their connectivity maps were also similar during seed-to-voxel analyses (i.e., superior frontal gyrus). Current results show that functional connectivity measures at a voxel level (ILC and fALLF) are already impacted in healthy aging. These findings imply that the functional compensations observed in healthy aging depends on the functional integrity of brain areas at a voxel level.